ABCB1 C3435T polymorphism is associated with tetrahydrocannabinol blood levels in heavy cannabis users. (April 2018) - Kebir, Oussama; Lafaye, Genevieve; Blecha, Lisa; Chaumette, Boris; Mouaffak, Fayçal; Laqueille, Xavier; Benyamina, Amine
Abstract: ABCB1 polymorphisms are known to modify drug pharmacokinetics but have yet to be studied for their role in generating and maintaining cannabis dependence. The objective of this study is to determine if ABCB1 C3435T (rs1045642) polymorphism may modulate Δ9-Tetrahydrocannabinol (THC) blood levels in a sample of heavy cannabis users. The study sample includes 39 Caucasian individuals, recruited in two French addictology centres, with isolated cannabis dependence and heavy use (defined as ≥ 7 joints per week). Each underwent clinical evaluation, cannabis blood metabolite dosage (THC, 11-OH-THC, and THC-COOH) and genotyping of ABCB1 C3435T polymorphism. In this population (males: 74.4%, average age 29.5 +/− 9), average cannabis use was 21 joints per week (median 12; range 7 – 80). T carriers (TT/CT) had significantly lower plasma THC levels (ng/ml) versus non T carriers (8 vs 15.70, significant), controlling for level of weekly use, 11-OH-THC and THC-COOH levels. Our results show that ABCB1 C3435T polymorphism may modulate serum THC levels in chronic heavy cannabis users. The exact mechanisms and roles that this may play in cannabis dependence genesis and evolution remain to be elucidated. These results should be controlled in a replication study using a larger population.